2016
DOI: 10.13075/ijomeh.1896.00667
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of bronchiectasis cases in Silesian voivodeship in 2006–2010

Abstract: Objectives: Reports on an increasing number of hospitalizations in other European countries and the lack of epidemiological data on the prevalence of bronchiectasis in Poland constituted motivation for the authors to investigate temporal changes of the registered incidence and hospitalization due to bronchiectasis in Silesian voivodeship, and to evaluate spatial variability of the disease in the study region. Material and Methods: The study is a descriptive epidemiological project. Temporal and spatial variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…One study identified as an abstract in the systematic review has subsequently been published as a full paper [9]. Fifteen studies included > 200 patients; of these, six were conducted in the USA [914], three in the UK [1517], two in Spain [18, 19], and the others in New Zealand [20], Germany [21], Poland [22], and Singapore [23]. All studies involved adults and one included children [20] and a second included individuals of any age.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study identified as an abstract in the systematic review has subsequently been published as a full paper [9]. Fifteen studies included > 200 patients; of these, six were conducted in the USA [914], three in the UK [1517], two in Spain [18, 19], and the others in New Zealand [20], Germany [21], Poland [22], and Singapore [23]. All studies involved adults and one included children [20] and a second included individuals of any age.…”
Section: Resultsmentioning
confidence: 99%
“…[12, 14]. Twenty-two further studies reported on hospitalization rates or length of stay for patients with bronchiectasis; [9, 11, 1322, 24–33] some of these studies also reported on other aspects of resource use. Eight studies report the costs of managing bronchiectasis and provide evidence for cost drivers in this disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation